Actor-Network Theory in Policy Change of Environmental Permit Policy for the Construction of a Cement Factory in Pati, Indonesia - Ibnu Fath Zarkasi; Ramaditya Rahardian (Department of Government Studies Universitas Muhammadiyah Makassar, 2022)
The determining factor in the success and failure of advocacy is the support network in a coalition formed in policy advocacy. This study analyzes the Kendeng Mountains Community Caring Network in refusing an environmental permit for the construction of a cement factory in Kendeng Mountains, Pati, Indonesia. The government issued the Decree of the Regent of Pati No. 660.1/4767/2014 regarding the environmental permit for the construction of a cement factory. On the other hand, the people around the Kendeng Mountains who have inhabited the area for a dozen years are worried about the plan to build a cement factory that will threaten the ecological balance. The approach used in this study was the Actor-Network Theory of Michael Callon as it can see the phenomenon of the network formed by a Civil Society Organization (CSO) in rejecting the policy of developing the cement industry in their area. This study employed a qualitative method that stands on an interpretive paradigm. Data were collected by observation, documentation, in-depth interviews, and Focus Group Discussion (FGD). The results of this study showed that based on numerous dynamics of the overall use of existing network access, coalition actors have succeeded in proposing the desired policy changes in the form of stricter regulations. These winning coalitions are more often involved in a variety of strategies and have greater public support. Finally, this study contributes significantly to the usefulness of the Actor-Network Theory approach in policy change.